PW 0913 Cost of older adult falls in the united states and innovative interventions to address the problem. (November 2018) - Lee, Robin; Bergen, Gwendolyn; Burns, Elizabeth; Florence, Curtis; Johnston, Yvonne; Dellinger, Ann; Baldwin, Grant
Abstract : Background: Falls are projected to be the 17th leading cause of death globally by 2030. Older adults are disproportionately affected. In the United States (U.S.), one in four adults 65+fall annually. By 2030, there will be 49 million falls among older adults and 12 million injuries in the U.S. each year. Description of the problem: When not fatal, falls can cause brain injury, hip fracture, and loss of independence. In the U.S., there are more than 3 million emergency department visits, and over 8 00 000 hospitalizations each year due to falls. However, falls can be prevented. This presentation describes the overall cost of older adult falls in the U.S. and innovative approaches the U.S. Centers for Disease Control and Prevention (CDC) is pursuing to address this major health threat. Cost of older adult falls: In total, $50 billion was spent to treat nonfatal falls in 2015, with government-funded programs (Medicare, Medicare) paying 75% of the total. Medical spending for fatal falls was $750 million. Most U.S. adults age 65+receive healthcare coverage through Medicare, a federally funded program. On average, Medicare pays approximately $10 000 per emergency department visit and $30 000 per fall-related hospital stay. CDC approach: Given the health and economic burden, CDC encourages healthcare providers to screen, assess, and intervene to reduce patient's multiple fall-risk factors. Interventions that address multiple modifiable risk factors can reduce falls by 24%. The CDC is evaluating the effectiveness of clinical fall prevention in primary care, upon hospital discharge, and within community pharmacies. In primary care, older adults at risk for a fall who received a treatment plan to reduce their fall-risk were 40% less likely to have a fall-related hospitalization compared to those at-risk without a treatment plan. Conclusion: Fall interventions offered in clinical settings can reduce healthcare expenditures and prevent falls worldwide.